2018
DOI: 10.1080/16549716.2018.1423862
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting effective ventilation during newborn resuscitation: a qualitative study among midwives in rural Tanzania

Abstract: Background: Intrapartum-related hypoxia accounts for 30% of neonatal deaths in Tanzania. This has led to the introduction and scaling-up of the Helping Babies Breathe (HBB) programme, which is a simulation-based learning programme in newborn resuscitation skills. Studies have documented ineffective ventilation of non-breathing newborns and the inability to follow the HBB algorithm among providers. Objective: This study aimed at exploring barriers and facilitators to effective bag mask ventilation, an essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 35 publications
5
42
0
2
Order By: Relevance
“…This implies the benefit of the preparation of essential equipment, and sometimes staff for unforeseeable and foreseeable resuscitations helps them to start ventilation on time, and increases the chances of a baby surviving after resuscitation. By improving the availability and readiness of NR equipment, Ethiopia can reduce barriers to the proper neonatal resuscitation practice and improve performance that impact to decrease high neonatal mortality in the country [17]. This is supported by evidence from an effective intervention to decrease global neonatal mortality; effective NR could prevent neonatal deaths by 30% as well as improve the outcomes of newborns delivered with birth asphyxia [18].…”
Section: Discussionmentioning
confidence: 98%
“…This implies the benefit of the preparation of essential equipment, and sometimes staff for unforeseeable and foreseeable resuscitations helps them to start ventilation on time, and increases the chances of a baby surviving after resuscitation. By improving the availability and readiness of NR equipment, Ethiopia can reduce barriers to the proper neonatal resuscitation practice and improve performance that impact to decrease high neonatal mortality in the country [17]. This is supported by evidence from an effective intervention to decrease global neonatal mortality; effective NR could prevent neonatal deaths by 30% as well as improve the outcomes of newborns delivered with birth asphyxia [18].…”
Section: Discussionmentioning
confidence: 98%
“…Key themes in this manuscript, including facility infrastructure and resources, referral processes, cultural norms, traditional practices, hierarchy, interpersonal relations, and poverty have been previously described as common barriers to neonatal care in LMICs in multi-country analyses [ 7 – 9 , 11 ] and in qualitative evaluations of the Helping Babies Breathe program [ 27 , 28 ]. However, to our knowledge, this is the first in-depth characterization of these barriers in Bihar.…”
Section: Discussionmentioning
confidence: 99%
“…However, mentors in this study additionally identified functionality and accessibility of already available supplies as equally important issues. While ensuring the consistent availability of supplies such as mucus extractors, preterm-size masks, and clean towels is essential, training providers on delivery preparedness and handover techniques may improve the accessibility and timely utilization of already available equipment [ 28 ]. Moreover, ensuring a more reliable power supply at PHCs would facilitate use of available radiant warmers and oxygen concentrators when indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Psychologically, midwives face a huge work-related emotional burden including that of dealing with the contradictory feelings of fear, anxiety, anger and sadness that come with medical emergencies as well as the excitement and happiness that they feel during the safe birth of healthy babies (17)(18)(19). Other psychological consequences of barriers to midwives' ability to provide quality care include constant stress, desperation, insecurity, anxiety and demotivation (15,20).…”
Section: Introductionmentioning
confidence: 99%
“…Midwives' anxiety is believed to sometimes engender panic attacks (21). Members of the profession have also been found to exhibit depression and symptoms of post-traumatic stress disorder as a consequence of dealing with traumatic events (17,22).…”
Section: Introductionmentioning
confidence: 99%